SYSTEMATIC LITERATURE REVIEW: STRATEGI GREEN MARKETING DALAM MENINGKATKAN KESADARAN LINGKUNGAN DAN MINAT BELI STARBUCKS COFFEE - Rahman, Aldi; Andika Agus Yudistira; Fenty Fauziah; Lorine Kalista Noor (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2024)
The use of plastic replacing other materials exacerbates marine pollution, accumulation of nondegradable waste, and leads to greenhouse gas emissions and microplastics, threatening ecosystems and human health. This study aims to analyze the effectiveness of green marketing strategies in enhancing environmental awareness and purchasing interest in Starbucks Coffee products. The research methodology employs Systematic Literature Review (SLR), collecting data through documentation of relevant articles from similar studies. Findings indicate that green marketing effectively boosts purchasing interest and positively impacts brand image, influencing consumer purchasing decisions and loyalty